1999
DOI: 10.1002/jlb.66.6.1005
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TNF-α receptors bind and neutralize over-expressed transmembrane TNF-α on macrophages, but do not inhibit its processing

Abstract: Tumor necrosis factor alpha (TNF-alpha) is initially synthesized as a type II integral membrane protein (transmembrane TNF-alpha) after macrophage activation. In this study we have investigated some aspects of the regulation of expression and biological activity of transmembrane TNF-alpha by both soluble TNF-alpha receptors (sTNF-alphaR) and inhibitors of TNF-alpha processing. We show, using the technique of receptor-mediated ligand precipitation (RMLP), that a dimeric construct of the type I sTNF-alphaR binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
(59 reference statements)
0
15
0
1
Order By: Relevance
“…A corollary of these evidences is that TNF-␣ overproduction resulting from stress-induced TACE up-regulation could mediate the induction of iNOS. Indeed, BB1101, a preferred inhibitor of metalloproteinases with sheddase activity (Kupatt et al 1999;Watts et al 1999) inhibited not only stress-induced TNF-␣ release but also the expression of iNOS as demonstrated at the level of iNOS activity and protein, suggesting that TNF-␣ is involved in the expression of this NOS isoform in our model.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A corollary of these evidences is that TNF-␣ overproduction resulting from stress-induced TACE up-regulation could mediate the induction of iNOS. Indeed, BB1101, a preferred inhibitor of metalloproteinases with sheddase activity (Kupatt et al 1999;Watts et al 1999) inhibited not only stress-induced TNF-␣ release but also the expression of iNOS as demonstrated at the level of iNOS activity and protein, suggesting that TNF-␣ is involved in the expression of this NOS isoform in our model.…”
Section: Discussionmentioning
confidence: 62%
“…injected with BB1101 (a TACE inhibitor; Kupatt et al 1999;Watts et al 1999), with MK-801 ([(ϩ)-5-methyl-10,11-dihydroxy-5H-dibenzo (a,d) cyclohepten-5,10-imine]; dizocilpine), a specific non-competitive NMDA antagonist (Wong et al 1988) or with PDTC (pyrrolidine dithiocarbamate, an inhibitor of the activation of NF-B; Schreck et al 1992). Drugs were administered at the onset of the stress.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
“…1b). Irrespective to the presence of functional TNF-R1 receptors on plasma membrane of COLO 205 cells [17] it was previously reported that these cells are resistant to apoptotic stimuli induced by TNF-a [7]. Therefore it is obvious that the incubation of COLO 205 cells with a physiological concentration of TNF-a (10 ng/ml) had no detectable effect on cell morphology (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…1). Irrespective to the presence of functional TNF-R1 receptors on plasma membrane of COLO 205 cells [21] it was previously reported that the cells are resistant to apoptotic stimuli induced by TNF-a [13]. Therefore, it is obvious why the incubation of COLO 205 cells with a physiological concentration of TNF-a [10 ng/ ml] had no detectable effect on cell morphology (Fig.…”
Section: Sodium Butyrate Potentiates Tnf-a-mediated Apoptosismentioning
confidence: 89%
“…From this point of view, sodium butyrate (NaBt) is believed to modulate the resistance of human colon adenocarcinoma COLO 205 cells to TNF-a-induced apoptosis [21,27]. Cytotoxic drugs often induce cell death via the up-regulation of death receptors [28].…”
Section: Discussionmentioning
confidence: 99%